Overview of patient perceptions about caring in ignatius inpatient room, Santa Elisabeth Hospital Medan 2022 - Barus, Mardiati; Pujiastuti, Maria; Sianturi, Risma (Institute of Accounting Research and Novation (IARN), 2023)
Patient perception of nurse caring is a patient's assessment of nurses through attitudes, greetings, touching and listening to patient complaints by nurses when providing action or providing nursing services, nurse caring behavior is also important to help the patient's recovery process where a deep evaluation is need to Knowing the quality of nursing needs to be done by identifying the patient's perception of the caring behavior of the nurses they receive. The purpose of this study is to describe the patient's perception of caring for nurses in Ignatius Inpatient Room, Santa Elisabeth Hospital Medan 2022. This type of research use a descriptive approach. The population in this study were all inpatients as many as 257 patients. The sampling technique in this study used accidental sampling with the calculation of the Slovin formula as many as 35 respondents. The instrument use is a questionnaire about the caring behavior of nurses according to patient perceptions. The result of this study is that the patient's perception of caring nurses is in the good category as many as 35 patients (100%). It is expected that nurses can maintain caring behavior towards patients while still paying attention to the attitude of smiling and listening to patient complaints sincerely and sincerely.